SILENT MYOCARDIAL ISCHEMIA AND CARDIAC RHYTHM DISTURBANCES IN WOMEN WITH RHEUMATOID ARTHRITIS - D. S. Novikova; T. V. Popkova; A. N. Gerasimov; A. V. Volkov; E. I. Nasonov (Klinicist)
Objective: to assess the rate of silent myocardial ischemia (SMI) and the pattern of cardiac rhythm disturbances in women with rheumatoidarthritis (RA), their association with traditional risk factors (TRF) for cardiovascular diseases (CVD), with subclinical structural and functionalchanges in the heart and vessels, with the activity and severity of rheumatoid inflammation.Subjects and methods. Two hundred and ninety-one female patients aged less than 60 years with a valid diagnosis of RA and no clinicalsigns were examined. A control group consisted of 125 women without rheumatic diseases. In addition to the clinical manifestations, activity,and severity of RA, the authors assessed major TRFs for CVD, performed Holter ECG monitoring, common carotid artery duplex scanning, transthoracic echocardiographic study, and determined the levels of serum inflammatory markers.Results. The women with RA differ from the control group in the higher incidence of SMI, supraventricular arrhythmias (SVA) and highgradepremature ventricular contractions (PVC). The patients with RA and SMI are characterized in terms of age-adjustment by higher disease activity (DAS28), systemic manifestations), cumulative larger-dose glucocorticoids (GC) and a higher percentage of patients receiving disease-modifying anti-rheumatic drugs as compared with those with RA and no SMI with adjustment for age. High disease activity(DAS28, level of inflammatory markers), IgM rheumatoid arthritis seropositivity, and GC therapy are SVA-associated factors in women with RA; larger left ventricular end-diastolic dimension and serositis are factors associated with high-grade PVC.Conclusion. The RA women without clinical manifestations of CVD are recorded to have high rates of SMI, SVA, and high-grade PVC, which is primarily due to the activity and severity of rheumatoid inflammation.